Connecting for mompreneur success: The essential role of quality of network ties and knowledge sharing across partners - Ardyan, Elia; Sentosa, Gwyneth Rachel (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2025)
Knowledge sharing activity and quality of network ties play a crucial role for mompreneurs as it provide essential support, resources, and opportunities for performance growth. This study aims to examine, from the perspective of women entrepreneurs (mompreneurs), the impact of the quality of mompreneur network ties and knowledge sharing across networks on product innovation, and business performance. This study investigates mompreneurs in the tourism industry, particularly several tourist destinations in Yogyakarta, Indonesia. This study's samples consist of 167 mompreneurs in the tourism industry. We analyzed the data using structural equation modeling partial least squares (SEM-PLS) and WarpPLS version 8.0 was used to process the data. We utilize SEM-PLS due to the relatively small sample size of 167 tourism industry owners or managers. The findings of this study indicate that the quality of mompreneur network ties has a significant impact on knowledge sharing across networks, product innovation, and business performance. Other findings indicate that knowledge sharing across networks positively and substantially affects product innovation. This research offers insights into enhancing the performance of SME enterprises operated by mompreneurs.